Genetic control of greenhouse gas emissions. (19th October 2016) - de Haas, Y.; Garnsworthy, P. C.; Kuhla, B.; Negussie, E.; Pszczola, M.; Wall, E.; Lassen, J.
Abstract : Climate change is a growing international concern, and it is well established that the release of greenhouse gases (GHG) is a contributing factor. So far, within animal production, there is little or no concerted effort on long-term breeding strategies to mitigate against GHG from ruminants. In recent years, several consortia have been formed to collect and combine data for genetic evaluation. The discussion areas of these consortia focus on (1) What are methane-determining factors, (2) What are genetic parameters for methane emissions, (3) What proxies can be used, and what is their association with methane emission, and (4) How to move on with breeding for lower emitting animals? The methane-determining factors can be divided into four groups: (1) rumen microbial population, (2) feed intake and diet composition, (3) host physiology and (4) host genetics. The genetic parameters show that enteric methane is a heritable trait, and that it is highly genetically correlated with dry matter intake. So far, the most useful proxies relate to feed intake, milk mid IR spectral data and fatty acids in the milk. To be able to move on with a genetic evaluation and ranking of animals for methane emission, it is crucial to make measurements on commercial farms. In order to make that possible, it will be necessary to develop phenotypes that can be used by the farmer to optimise the production on farm level. Also, it is crucial to develop equipment that makes it possible to make measurements without interfering with everyday routines or identify proxies that are highly related to methane and which could easily be measured on a large scale. International collaboration is essential to make progress in this area. This is both in terms of sharing ideas, experiences and phenotypes, but also in terms of coming to a consensus regarding what phenotype to collect and to select for.